Acute chylous peritonitis due to idiopathic pancreatitis mimicking acute appendicitis - Dan Bratu; Alin Mihetiu; Dragoș Virgil Davițoiu; Vlad Dumitru Băleanu; Liliana Florina Andronache; Oana Popescu (Journal of Mind and Medical Sciences)
The acute development and the accumulation of chyle into the peritoneal space is a rare condition and one needs to be able to distinguish it from chylous ascites, which is most commonly chronic and associated with related diseases. It is frequently idiopathic and additionally, clinical and imaging findings are nonspecific. In almost all cases, the diagnosis is made intraoperatively during laparoscopy or laparotomy, most diagnostic procedures being indicated by acute complaints pertaining to the abdomen. A 23-year-old man was admitted to the Emergency Department with abdominal pain, with right iliac fossa tenderness and peritonism. Laparoscopy was performed due to acute abdomen findings. Further exploration revealed chylous effusion with milky-like fluid. The peritoneal lavage and the insertion of drains were subsequent to the careful inspection of the cavity. The biochemical analysis of the peritoneal fluid was an important aid which provided the diagnosis of chylous peritonitis due to acute pancreatitis.